2017
DOI: 10.1002/jcb.26080
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Breast Cancer GWAS Loci Identifies the Putative Deleterious Effect of STXBP4 and ZNF404 Gene Variants

Abstract: The genome-wide association studies (GWAS) have enabled us in identifying different breast cancer (BC) susceptibility loci. However, majority of these are non-coding variants with no annotated biological function. We investigated such 78 noncoding genome wide associated SNPs of BC and further expanded the list to 2,162 variants with strong linkage-disequilibrium (LD, r ≥0.8). Using multiple publically available algorithms such as CADD, GWAVA, and FATHAMM, we classified all these variants into deleterious, dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Despite generally good prognosis for BC patients, there is a wide variation in survival [1]. Some of the common risk factors for BC include age, genetic background, hormonal factors, reproductive and menstrual history, excessive alcohol consumption, radiation, benign breast disease, and obesity [2]. Genetic variation has been shown to affect both susceptibility and prognosis of BC [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite generally good prognosis for BC patients, there is a wide variation in survival [1]. Some of the common risk factors for BC include age, genetic background, hormonal factors, reproductive and menstrual history, excessive alcohol consumption, radiation, benign breast disease, and obesity [2]. Genetic variation has been shown to affect both susceptibility and prognosis of BC [1].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation has been shown to affect both susceptibility and prognosis of BC [1]. Genome wide association studies (GWAS) have recently been used to identify new loci for BC, and so far almost 100 loci have been identified [2]. In addition to providing new prognostic markers, genetic determinants of prognosis can also give new biological insight for progression of BC [3].…”
Section: Introductionmentioning
confidence: 99%
“…Even though there were respective 18 (56.25%) and 2 (100%) independent TWAS genes of breast and ovarian cancer by PrediXcan also identified by TIGAR (see Figure S11 and Tables S8, S9, S10), only TIGAR identified the novel TWAS genes UBE2MP1 and FRG1EP shared by both breast and ovarian cancer and the known GWAS risk genes FGF10 [11,58] and TOX3 [36,38] of breast cancer. Other exclusive independent TWAS genes identified by TIGAR include lncRNA RP11-758M4.4 which was shown to be a potential biomarker of breast cancer [59], RPS23 which was found to be over-expressed in advanced colorectal adenocarcinomas [60], and ZNF404 whose dysregulation was linked to breast cancer pathogenesis by eQTL analyses [61,62].…”
Section: Compare With Twas Results By Predixcanmentioning
confidence: 99%
“…Other exclusive independent TWAS genes identified by TIGAR include lncRNA RP11-758M4. 4 which was shown to be a potential biomarker of breast cancer 68 , RPS23 which was found to be over-expressed in advanced colorectal adenocarcinomas [MIM: 114500] 69 , and ZNF404 whose dysregulation was linked to breast cancer pathogenesis by eQTL analyses 70,71 . Potentially novel TWAS risk genes by PrediXcan and TIGAR that were not identified by previous GWAS are presented in Table S11.…”
Section: Twas Of Breast and Ovarian Cancermentioning
confidence: 99%
“…Recent genome-wide association studies (GWAS) and improved single-nucleotide polymorphism (SNP) analyses have revealed hundreds of common genetic mutations closely related to T2DM. However, the relationship between gene polymorphism and the occurrence of T2DM, as well as its underlying mechanism, is still unclear [ 2 , 3 , 4 , 5 ]. Consequently, the etiology and pathogenesis of T2DM have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%